Pengolahan Limbah Cair Industri Pulp Dan Kertas Dengan Metode SRAOP (Sulfate Radical-Advanced OxidationProcess) Menggunakan Katalis Nanomaterial Cobalt Framework (Co@NC) - Eka Trisnawati; Edy Saputra; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Catalyst cobalt nanomaterial (Co@NC) was prepared by MOF strategy using rhombic dodecahedral cobalt based on Zeolitic Imidazolate Framework -67 (ZIF-67) as an effective precursor and template. Co@NC was successfully synthesized by reacting cobalt (II) nitrate and 2-methylimidazole with methanol solvent at room temperature and allowed to stand for 48 hours at room temperature to form a purple solid. Then it is carbonized at 600oC for 6 hours with argon. Their properties were characterized by X-ray diffraction (XRD). The Catalyst Co@NC catalyst has 4 peaks that appear at an angle of 2θ: 44.24 °, 51.70 °, 71.03 °, 79.73 ° which are perfectly indexed to the metal characteristics of Co [JCPDS File No. 89-4307]. The catalyst activity of Co@NC was evaluated for the oxidation degradation of organic compounds in the pulp and paper industrial wastewater with radical sulfate. Effect of catalyst concentration (0; 0.1; 0.2; 0.3; 0,4 g/L) and reaction time 120 minutes was investigated in this study. The optimum conditions with the percentage of COD removal reached 80,92% obtained at 120 minutes, catalyst concentration 0.4 g/L, concentration of peroxymonosulfate 2 g/L, reaction temperature of 30oC. Therefore, the Co@NC nanomaterial is very feasible as a catalyst in industrial applications that will be used for wastewater treatment effectively. Keywords: AOP, COD, MOF, Nanomaterial, Wastewater